The Sub-Ice Structure of Mt. Melbourne Volcanic Field (Northern Victoria Land, Antarctica) Uncovered by High-Resolution Aeromagnetic Data - Ghirotto, Alessandro; Armadillo, Egidio; Crispini, Laura; Zunino, Andrea; id_orcid:0 000-0002-3415-162X; Tontini, Fabio C.; Ferraccioli, Fausto (Wiley-Blackwell, 2023)
The Mt. Melbourne Volcanic Field is a quiescent volcanic complex located in Northern Victoria Land, Antarctica, mostly covered by ice. Its inner structure has remained largely unknown, due to the paucity of outcrops and the lack of detailed multi-disciplinary investigations. Here we present a novel high-resolution aeromagnetic dataset, revealing strong long-wavelength negative anomalies superimposed by short-wavelength positive ones forming characteristic radial patterns. Automatic lineament detection, through the Hough transform technique applied to the tilt derivative of our magnetic dataset, shows prevailing NW-SE-to NNE-SSW-trending structural features, which combined with the few structural field observations contribute to define the deformation pattern. Pre-existing and novel magnetic property measurements, coupled with available geochronological data, are used to constrain a two-step 3D magnetic inversion. A layer-structured Oldenburg-Parker's inversion was utilized to model the deep and long-wavelength components of the magnetic field, whereas a linear inversion based on a set of shallower prisms was used to model the short-wavelength components. The final 3D model shows widespread reversely-polarized volcanics, which are locally intruded and superimposed, respectively by swarms of normally-polarized dikes and radial lava flows along paleo-valleys. These results support the onset of volcanic activity in the entire field at least in the Matuyama magnetic epoch, that is, between 2.58 and 0.78 Ma. ISSN:2169-9313 ISSN:0148-0227 ISSN:2169-9356